Patient Pathway Across Portuguese Emergency Network: What Matters for Health Outcomes? - Mendes, João (Gazeta Médica, 2022)
INTRODUCTION: Regional inequalities in access and health results have become a relevant issue in all developed countries. In this paper it was sought to evaluate possible disparities due to geographical localization, in cases of acute and severe illness. MATERIAL AND METHODS: By accessing the logbook of the emergency room of the polyvalent emergency service (PES) in Viseu, Portugal, detailed information was extracted from 2812 episodes that occurred during 2019. This sample also includes users from two medical and surgical emergency services (MSES), which serve Guarda and Covilhã regions, as well as three basic emergency services (BES). It was used a retrospective design and logistic regression models were estimated to assess differences in mortality. RESULTS: Our data prove the existence of a protective effect of BES (p-value = 0.031) and an adverse impact of distance, particularly in cases of stroke (p-value = 0.027). In addition, we did not find difference in 30-day mortality between patients from Guarda, Covilhã and Viseu regions (p-value = 0.536). CONCLUSION: This study is pioneer in demonstrating the importance of BES. Furthermore, it confirms that the creation of reference centers contributes to the improvement of outcomes, with no difference in mortality of patients who are initially approached by lower differentiation centers.